THE GLOBAL IMPACT OF RUSSIAN AEROSPACE CLOSURE - Chairussani Abbas Sopamena (Universitas Jenderal Ahmad Yani, 2022)
The war between Russia and Ukraine has a long tail and has spawned sanctions between countries. Aggressive Russia has taken the decision to close their airspace for many countries which became a policy that brought the world back to the similar conditions that happen in the cold war era. This article is written to answer the question, what is the impact of the closure of Russian airspace on the airline industry and the world economy? With using realism and structural functionalist approach this research shows that Russia's actions are taken to as a way deter other countries which support Ukraine. Thus, it is a clear indication that the existing international institutions along with their international law are indeed failed in dealing with the tendency of states (Russia) to act aggressively and halt their misconduct on their international interactions.